Valuation of Social Capital and Environmental Externalities - Iulie Aslaksen; Kjell Arne Brekke (Statistics Norway, Research Department, 2000)
The transition from more traditional to modern modes of production has large implications for time allocation, accumulation of social capital, market and non-market production, consumption, as well as for the environmental externalities of production and consumption. In this paper we explicitly take into account the time allocation aspect in the formation of social capital. We analyze how time allocation, accumulation of social capital and production depend on the productivity in the transformation of time to social capital, productivity of social capital in the production of commodities and valuation of social capital. We find that a higher valuation of social capital does not necessarily lead to more leisure or other non-market activities, reduced consumption and potentially improved environment, the relationship is highly sensitive to the assumptions about accumulation of social capital.
Keywords: J22; D62; 330; Time allocation; Social capital; Environmental externalities